Enhanced superconductivity accompanying a Lifshitz transition in electron-doped FeSe monolayer - X. Shi; Z-Q Han; X-L Peng; P. Richard; T. Qian; X-X Wu; M-W Qiu; S. C. Wang; J. P. Hu; Y-J Sun; H. Ding (Nature Communications, 2017)
The origin of superconductivity enhancement in FeSe monolayer grown on SrTiO3 compared to bulk FeSe is still a debated issue. Here, Shi et al. report a further 15 K jump of Tc accompanying a second Lifshitz transition triggered by electron doping in FeSe/SrTiO3monolayer films.